2021
DOI: 10.3389/fsurg.2021.691473
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy After Radical Prostatectomy: What Has Changed Over Time?

Abstract: The role and timing of radiotherapy (RT) in prostate cancer (PCa) patients treated with radical prostatectomy (RP) remains controversial. While recent trials support the oncological safety of early salvage RT (SRT) compared to adjuvant RT (ART) in selected patients, previous randomized studies demonstrated that ART might improve recurrence-free survival in patients at high risk for local recurrence based on adverse pathology. Although ART might improve survival, this approach is characterized by a risk of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In addition, many patients with low volume LNI may continue to receive excessive and potentially unnecessary post-operative therapy [26,27]. For example, in 2021 Zattoni et al reported that although adjuvant radiation therapy may improve recurrence-free survival compared to salvage therapy in patients with high risk for local recurrence, up to 40% of patients could be overtreated [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many patients with low volume LNI may continue to receive excessive and potentially unnecessary post-operative therapy [26,27]. For example, in 2021 Zattoni et al reported that although adjuvant radiation therapy may improve recurrence-free survival compared to salvage therapy in patients with high risk for local recurrence, up to 40% of patients could be overtreated [28].…”
Section: Discussionmentioning
confidence: 99%
“…This review focused on radiotherapy, however there are other treatments for prostate cancer including hormone therapy, prostatectomy and combinations therein, though optimal timing of these combinational therapies appears unclear [ 96 , 97 ]. There have been recent advances in using sophisticated machine learning/artificial intelligence (ML/AI) techniques on imaging data to predict whether patients require biopsies, or to predict clinical failure or death under these alternative treatment pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Histology and risk factors are important in determining PSA levels to initiate salvage radiation therapy. 31,32 Results from the RADICALS trial showed no additional benefit with adjuvant radiation therapy after radical prostatectomy compared with early salvage radiation therapy for PSA biochemical progression. 33 Individual consideration is important before suggesting adjuvant or salvage radiotherapy in prostatectomy patients based on factors such as PSA levels, Gleason score, adverse risk factors, nodal status, and the postoperative clinical condition of the patient.…”
Section: Cuaj -Specialmentioning
confidence: 99%